Climate Youth Activism Initiatives: Motivations and Aims, and the Potential to Integrate Climate Activism into ESD and Transformative Learning - Matthias Kowasch (MDPI AG, 2021)
For about two years, the climate youth activism initiative Fridays for Future has addressed climate emergency, receiving considerable attention because of their consistent protests every week in many different locations worldwide. Based on empirical studies in Austria and Portugal, this paper investigates the motivations of students to participate in the movement and the solutions proposed by young activists to fight against climate emergency. Moreover, we discuss the integration of climate change activism into ESD (education for sustainable development) and transformative learning processes, and how this enables environmental citizenship. The results of the studies reveal that emotions and feelings of solidarity and collective aims are motives to participate in the strikes. The young activists sometimes propose innovative and sometimes radical solutions to climate emergency. Both demonstrations and exhibitions as forms of bottom-up climate activism initiatives contribute to engagement in political dialogue and scientific knowledge transfer. They can be seen as “triggers of change” for transformative learning.